Transanal endoscopic microsurgery: indications and results after 100 cases - Palma, Pablo; Freudenberg, Sebastian; Samel, Stephan Tim; Post, Stefan (Colorectal disease, 2004)
Objective Transanal endoscopic microsurgery (TEM), a minimally invasive technique has been employed in the excision of benign and well-selected malignant rectal tumours since June 1998. We present a prospective descriptive study and analyse the currently accepted indications. Patients and methods Over a 4-year period 100 patients underwent TEM for treatment of rectal tumours located between 4 and 18 cm from the anal verge. Results TEM was performed in 71 cases for adenomas, 20 potentially curative excisions for pre-operative staged low-grade carcinoma, 3 palliative procedures for advance carcinoma, 5 carcinoids and 1 solitary ulcer. The local complication rate included wound breakdown in 7 patients, three of them requiring ileostomy. Conversion to laparotomy was performed in two patients. Five adenomas recurred and were successfully treated by TEM. Of the cancers, four patients required immediate salvage therapy by means of total mesorectal excision. Three patients underwent palliative TEM procedures combined with radiotherapy. A single cancer recurrence was treated by means of abdomino-perineal resection after radiotherapy. Conclusions TEM appears to be an effective method of excising benign tumours and selected T1 carcinomas of the rectum. The superior exposure of tumours higher in the rectum combined with the greater precision of excision make this minimally invasive technique an attractive surgical approach.